Death Penalty - Mitrović, Ljubinko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
The system of criminal sanctions is one of the most, if not the most important, questions of substantive criminal law in general, including the Republic of Srpska and Bosnia and Herzegovina. This system is also characterized by its constant changes in terms of establishing new and the disappearance of some, often many years krivičnh sanctions. A special place in the system of criminal sanctions occupies a system of punishment that is characterized by the fact that contemporary criminal law for many years, so do not anticipate. Corporal punishment, on the other hand, is a punishment that has been abolished or repealed in an increasing number of countries, as it consists of the deprivation of life for committing a crime in a legal manner, especially when the perpetrator is guilty of criminal offences. It is about the death penalty, its application today, as well as international organizations fighting for the repeal, that will be discussed in this paper.